MPFL reconstruction vs. Insall procedure for adolescent patellar instability: nine-year follow-up on osteoarthritis, redislocations, and return to sports - Jääskelä, Maija; Perhomaa, Marja; Lempainen, Lasse; Sinikumpu, Jaakko (BMC, 2026)
Background: Medial patellofemoral ligament reconstruction (MPFLR) has become increasingly common in treating patellofemoral instability (PFI). Previously, proximal realignment surgeries, such as Insall's procedure, were preferred in adolescents with open physes. More evidence is needed on the long-term outcomes of MPFLR and Insall's procedures, particularly regarding the risk of early postoperative osteoarthritis and redislocation.
Methods: A total of 129 patients under 17 years of age who underwent surgery for PFI between 2005 and 2019, with a minimum follow-up time of 24 months, were retrospectively evaluated. Inclusion criteria comprised isolated medial patellofemoral ligament reconstruction (MPFLR) or Insall's proximal realignment with at least partially open physes at surgery and residence within the hospital district to enable follow-up. Of the 129 patients, 31 met the inclusion criteria, and 24 patients (25 knees; 77%) participated in long-term clinical and radiographic follow-up. Most patients were female (62%) with a mean surgery age of 14.5 +/- 1.3 years. Osteoarthritis, redislocations, return to sports, subjective knee-specific recovery, and health-related quality of life were investigated. The mean follow-up time 9 years (range 2 to 18). The long-term outcomes were compared between the treatment groups.
Results: Patellofemoral osteoarthritis (Kellgren and Lawrence II-IV) was found in one knee (6.7%) after MPFLR and in six (60%) knees after Insall's procedure (P=.004). No tibiofemoral osteoarthritis was found after MPFLR but was present in four (40%) knees after Insall's (P =.008). No MPFLR patients required reoperation compared to a 40% (4/10) in the Insall's group (P=.008). At follow-up 26.7% (4/15) of MPFLR and 80% 8/10) of Insall's patients were unable to return in pivoting sports due to residual symptoms (P=.008). No significant differences were found in IKDC (MPFLR 77.8 [SD 14.9] vs. Insall 's77.5 [SD 18.4], P= 0.973) or Lysholm scores (MPFLR 80.5 [SD 12.9] vs. Insall's 77.1 [15.2], P= 0.589).
Conclusion: MPFLR showed superior long-term outcomes compared to Insall's procedure in skeletally immature patients with recurrent PFI, with lower rates of osteoarthritis and reoperation.